2011
DOI: 10.1063/1.3652915
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-dependence of electronic grain boundary properties in polycrystalline CuInSe2 thin films

Abstract: The symmetry-dependence of electronic grain boundary (GB) properties in polycrystalline CuInSe2 thin films was investigated in a combined study applying scanning electron microscopy, electron backscatter diffraction, and Kelvin probe force microscopy. We find that highly symmetric Σ3 GBs have a higher probability to be charge neutral than lower symmetric non-Σ3 GBs. This symmetry-dependence can help to explain the large variations of electronic properties found for GBs in Cu(In,Ga)Se2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
6
32
0
Order By: Relevance
“…Moreover, the potential profile demonstrates that the S3 GB is charge neutral, because a potential dip or peak is not seen at the GB. This outcome is in accordance with the literature; S3 GBs have been reported as charge neutral due to the low defect density for this GB type [40][41][42]. In conclusion, our KPFM results suggest that the chemical fluctuations do not have an apparent effect on S3 GBs.…”
Section: Electron Backscatter Diffraction (Ebsd)supporting
confidence: 94%
“…Moreover, the potential profile demonstrates that the S3 GB is charge neutral, because a potential dip or peak is not seen at the GB. This outcome is in accordance with the literature; S3 GBs have been reported as charge neutral due to the low defect density for this GB type [40][41][42]. In conclusion, our KPFM results suggest that the chemical fluctuations do not have an apparent effect on S3 GBs.…”
Section: Electron Backscatter Diffraction (Ebsd)supporting
confidence: 94%
“…23 In contrast to other studies, where only one type 9,10,12 or two types 11 of GBs were reported, we observed three types in total on the same sample surface. This observation is consistent with a recent study of Baier et al 24 conducted on a CuInSe 2 sample. Fig.…”
supporting
confidence: 94%
“…It is a consistent result from all SEM [24][25][26][27][28] and SPM measurements 29,30 applied (in combination with EBSD) on grain boundaries in Cu(In,Ga)(S,Se) 2 thin films that most R3 (twin) boundaries do not exhibit substantial changes in the measured signals. Thus, most of these high-symmetrical types of grain boundaries are considered electrically inactive.…”
Section: Ebsd Combined With Other Scanning Microscopy Techniquessupporting
confidence: 60%